2018
DOI: 10.1590/1983-40632018v4853500
|View full text |Cite
|
Sign up to set email alerts
|

Growth and quality of Garcinia humilis seedlings as a function of substrate and shading level

Abstract: The successful establishment of a Garcinia humilis orchard depends on planting high-quality seedlings. This study aimed to evaluate the effects of the shading level (0 %, 18 % and 50 %) and substrate composition on the formation of G. humilis seedlings. Four substrates (S) were evaluated combining different proportions (v:v) of soil (SO), cattle manure (CM), commercial substrate (CS), sand (SA) and fine grain vermiculite (FV): S1 = 0 % SO + 45 % CM + 20 % CS + 20 % SA + 15 % FV; S2 = 15 % SO + 30 % CM + 20 % C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
3
7
1
Order By: Relevance
“…Similar to the present findings, high phosphorous content in foliage have been reported to increase insect growth rates (Frost & Elser, 2002;Perkins et al, 2004), improve survival probability (Clancy & King, 1993), fecundity (Popp et al, 1989), and population densities (Schade et al, 2003). The range of values of phosphorous content of dung in this study is similar to other reports of P content in cattle dung: 2.1 g kg −1 (Silva, 2008), 1.0 g kg −1 (Yolcu et al, 2010), 1.3 g kg −1 (Silva et al, 2018), and 1.71 g kg −1 (Costa et al, 2018), but less than the value of 5.5 g kg −1 reported by Higashikawa et al (2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the present findings, high phosphorous content in foliage have been reported to increase insect growth rates (Frost & Elser, 2002;Perkins et al, 2004), improve survival probability (Clancy & King, 1993), fecundity (Popp et al, 1989), and population densities (Schade et al, 2003). The range of values of phosphorous content of dung in this study is similar to other reports of P content in cattle dung: 2.1 g kg −1 (Silva, 2008), 1.0 g kg −1 (Yolcu et al, 2010), 1.3 g kg −1 (Silva et al, 2018), and 1.71 g kg −1 (Costa et al, 2018), but less than the value of 5.5 g kg −1 reported by Higashikawa et al (2010).…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of these trace elements varies in dung (Bolan et al, 2004), and the variation could be attributed to the age of an animal and type of food the animal eats (Irshad et al, 2013). The dung Mg levels reported in this study are lower than the average value of 5.3 g kg −1 of Mg reported by Higashikawa et al (2010), although there has been a wide range of values reported for the Mg content of cattle dung: 0.70 g kg −1 (Costa et al, 2018), 1.8 g kg −1 (Lima et al, 2006), 1000.0 mg kg −1 (Silva et al, 2018), and 88.0 mg kg −1 (Yolcu et al, 2010). In this study, high Mg concentrations in cattle dung collected in February 2018 corresponds to the month of maximum brood production by dung beetles.…”
Section: Discussionmentioning
confidence: 51%
“…Shading allows the microclimate within the environment to be differentiated and influences plant development (Áscoli et al, 2015(Áscoli et al, , Paula et al, 2017. Some species showed impaired growth in an environment without protection from direct solar radiation such as Garcinia humilis (Silva et al, 2018). For presenting morphophysiological characteristics adapted to this type of shaded environment, high exposures to light increases photo-oxidation and causes damage to the photosynthetic apparatus of plants, impairing its photosynthetic rate and, consequently, growth, as observed under the environment with 18-22 % of shading in the present study.…”
Section: Resultssupporting
confidence: 59%
“…The fruit also stands out for presenting high nutritional value, presenting in its composition antioxidant compounds as total phenolic compounds, vitamins and essential minerals. Therefore, it has high technological potential and can be used as raw material in various production processes (Silva et al, 2018;Tome et al, 2019).…”
Section: Introductionmentioning
confidence: 99%